Developing 10 Interesting Games as the Breakthrough of Monotonous Implementation of Flashcards to Vocabulary Learning and Assessments - Kusuma, I Putu Indra; Adnyani, Ni Luh Diah Surya; Taharyanti, Gusti Ayu Putu (Script Journal: Journal of Linguistic and English Teaching, 2017)
Vocabulary learning is the very first instructional process in learning a language. Vocabulary teaching has been becoming the issues of English teaching in Indonesia for years and it raises the opportunities of research on this field. This study belongs to Research & Development study which aims at (1) Describing the media used by teachers in vocabulary learning, (2) The activities implemented during the implementation of the media, and (3) Developing the games which can support the use of the media in vocabulary learning. The subjects in this study were teachers and 100 students of Elementary Schools in Buleleng Sub-district. This study used mixed methods approach where all the data was collected through the implementation of observations, interview, and administering questionnaires. The data was analyzed quantitatively and qualitatively. The results show that (1) the media used was flashcards, (2) the activity conducted was monotonous, and (3) 10 interesting games were developed. Based on the aforementioned results, it can be concluded that the media used by teachers was flashcards in which the implementation was monotonous. Therefore, 10 interesting games were developed.